Applicability of Thermophotovoltaic Technologies in the Iron and Steel Sectors. Issue 6 (3rd May 2018) - Utlu, Zafer; Paralı, Ufuk; Gültekin, Çağrı
Abstract: The theoretical potential for converting excess heat from the iron and steel sectors in Turkey into electricity by the use of thermophotovoltaic (TPV) systems is investigated and analyzed. The TPV usage in this industry is numerically investigated because this sector is in the leading position in terms of energy consumption in industrial sectors. Using the iron and steel industry waste heat energy data, it is shown that the energy conversion efficiencies of the TPV systems with the photovoltaic (PV) cell modules of In0.2 Ga0.8 As0.18 Sb0.82 and GaSb are 7.31 % and 2.04 %, respectively. When using TPV systems in the Turkish iron and steel sectors for waste heat energy potential, it is calculated that 29.88 MJ per year can be generated with GaSb cells, and 1.076 PJ per year can be generated with In0.2 Ga0.8 As0.18 Sb0.82 cells. Based on the results obtained from the numerical model in this study, some specific advice for the applicability and the development of the high efficiency TPV conversion systems is proposed. Abstract : The theoretical potential for converting excess heat from the iron and steel sectors in Turkey into electricity using thermophotovoltaic (TPV) systems is investigated and analyzed. Using the iron and steel industry waste heat energy data, the energy conversion efficiencies of the TPV systems with the photovoltaic (PV) cell modules of In0.2 Ga0.8 As0.18 Sb0.82 and GaSb are reported and the amount of electricity that could be generated using these cells is calculated. Based on the results, advice for the applicability and the development of the high efficiency TPV conversion systems is proposed.